COGNITIVE LEVELS OF INDONESIAN JUNIOR HIGH SCHOOL ENGLISH TEXTBOOK QUESTIONS: A REVISED BLOOM'S TAXONOMY ANALYSIS - Hidayat, Muhammad Yusril Rizqi; Rohmana, Wahyu Indah Mala (Journal of English Educational Study (JEES), 2025)
English textbooks play a crucial role in English Language Teaching (ELT) and cognitive development, particularly through the questions they incorporate, which is essential in shaping students’ analytical and reasoning skills. Previous studies have investigated the cognitive demands of textbook questions, where Lower-Order Thinking Skills (LOTS) are more prevalent than Higher-Order Thinking Skills (HOTS). This imbalance raises concerns regarding the effectiveness of textbooks in fostering students' critical thinking abilities. While these studies have primarily focused on specific sections or types of questions, there has been limited research examining the overall cognitive levels of all questions within a single textbook. This study aims to analyze the cognitive levels of the questions in the “English for Nusantara” textbook for eighth-grade students using Revised Bloom’s Taxonomy. Using a descriptive content analysis method both qualitative and quantitative approaches were used to classify and calculate the frequency of the cognitive levels.  The result of the study shows that the textbook is more inclined to LOTS than HOTS. In particular, comprehension (C2) was the most frequently used cognitive process (37.28%), followed by application (C3) (28.92%), while analysis (C4)  (11.50%), evaluation (C5) (3.48%), and generation (C6)  (8.36%) were used least frequently. This means that students are mostly engaged in the lower order cognitive processes such as comprehension and application. The study suggests that while the textbook supports basic language skills, it provides insufficient emphasis on critical thinking. Thus, curriculum developers and teachers should incorporate more HOTS-based questions to align with the Curriculum's objectives.